2012
DOI: 10.1037/a0028259
|View full text |Cite
|
Sign up to set email alerts
|

Therapist interventions and client innovative moments in emotion-focused therapy for depression.

Abstract: According to the narrative approach, change in self-narratives is an important part of successful psychotherapy. In this view, several authors have highlighted the usefulness of narrating new experiences (like actions, thoughts, and stories) during therapy in contrast with maladaptive client self-narratives. These new experiences are termed here innovative moments (IMs), and different types can be specified: action, reflection, protest, reconceptualization, and performing change. With the aim of understanding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
38
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 55 publications
(87 reference statements)
8
38
0
1
Order By: Relevance
“…Also in this phase of EFT, through the use of therapist exploration skills like reflection of feelings, the therapist may have facilitated client's distanced speech during the process of reflecting and transforming emotional responses: for example, when the therapist followed client reflections about the way she felt before and the differences regarding the way she feels now (closure statement of distancing speech). The predominance of exploration skills in this case is consistent with previous studies on EFT that show a high prevalence of this type of therapist interventions, congruently to the development of goodoutcome process of EFT (Cunha et al, 2012;GoatesJones, 2004;Goates-Jones et al, 2009).…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…Also in this phase of EFT, through the use of therapist exploration skills like reflection of feelings, the therapist may have facilitated client's distanced speech during the process of reflecting and transforming emotional responses: for example, when the therapist followed client reflections about the way she felt before and the differences regarding the way she feels now (closure statement of distancing speech). The predominance of exploration skills in this case is consistent with previous studies on EFT that show a high prevalence of this type of therapist interventions, congruently to the development of goodoutcome process of EFT (Cunha et al, 2012;GoatesJones, 2004;Goates-Jones et al, 2009).…”
Section: Discussionsupporting
confidence: 77%
“…Results indicated that exploration skills were more frequent than other skills across all different therapy phases of good and poor-outcome cases. Action and insight skills, although they were less frequent, occurred more often in poor-outcome cases than in good-outcome cases (Cunha et al, 2012). Yet, whereas Cunha and collaborators (2012), focused on client narrative change (through the presence of innovative moments in client speech), the present study looks specifically to the perspectives adopted in client speechi.e.…”
Section: The Present Study: Therapist's Interventions and Client's Immentioning
confidence: 99%
See 2 more Smart Citations
“…This approach indicates that auto-narrative changes are an important part of psychotherapeutic success. Moreover, authors have highlighted the usefulness of narrating new experiences (like actions, thoughts and stories) during therapy, contrasting with the customer's inadequate auto-narratives (Cunha et al, 2012). Therefore, along with possible influence of biological aspects, it is also possible that the more humanistic experience during the constructivist process of NCT is more suitable to female depression representations (Gonçalves & Machado, 1999).…”
Section: Discussionmentioning
confidence: 99%